The impact of pre professional practices in the tax culture of students of the Catholic University of Cuenca - Mendieta Andrade, Patricio (2020)
This paper analyzes the impact that the Accounting and Fiscal Support Core Project of the Catholic University of Cuenca has had on the tax culture of the students participating in it in the 2016-2018 period; for which the information from the Project database and the results of the survey planted to the students were used; being that, a positive impact on the knowledge, perceptions and attitudes towards taxes on the part of the students was evidenced after their participation in the Project was concluded, identifying the support of the teachers, as one of the factors that the students perceived, as the most influential in the identified impact. DOI: https://doi.org/10.31164/bcoyu.24.2020.885 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/885